Perceived Relationship Experiences Among Adolescents and Young Adult Women: Reproductive Coercion Pilot Study - Bonen-Clark, Rebecca Clare (East Carolina University, 2022)
Background: Reproductive coercion (RC) involves behavior that interferes with the individual’s unique ability to make decisions regarding reproductive health. It is intended to maintain power and control in a relationship by someone past, present, or future wishing to be involved in a relationship. RC has been associated with intimate partner violence, unintended pregnancy, and sexually transmitted infections. Additionally, it has been associated with depression and post-traumatic stress disorder. Prevalence estimates range from 3% to over 38%. There are three specific forms: contraceptive sabotage, pregnancy pressure, and control of pregnancy outcomes. The goal was to better understand the concept of RC among adolescents and young adult women (14-26 years) seeking services in primary or public health settings in Indiana and North Carolina. Methods: An anonymous Qualtrics survey was utilized to collect data on self-reports of contraceptive sabotage, pregnancy pressure, and control of pregnancy outcomes. Study participants were recruited through a generated QR code that was shared through posters, flyers, and social media posts. Data were collected between 5/4/20 to 12/31/20. IRB approval was obtained. Results: The survey had 73 participants with 63 completing the survey. We found a RC prevalence of 8% among this sample with almost 2% reporting more than one form. Women who reported RC were less likely to report using a more effective method of contraception (11.1% vs. 6.5%), more likely white (60%), and live in a rural setting (60%). They were also more likely to have a partner who was older (66.7% vs. 35.7%). In addition, those who reported RC were more likely to report being “unhappy” (22.2%) vs. “happy” (2.3%) (p=0.024). Conclusions: This pilot study found a prevalence of RC among this population. Reproductive coercion is a relatively new concept; but it plays a vital role in the sexual/reproductive health of the clients we serve.
Keywords: Reproductive Coercion